2016
DOI: 10.1159/000448395
|View full text |Cite
|
Sign up to set email alerts
|

Does Schizophrenia in Offspring Increase the Risk of Developing Alzheimer's Dementia

Abstract: Background/Aims: Prior studies have consistently found a higher risk of dementia in individuals with schizophrenia, but whether this is due to a common etiology between the disorders remains obscure. We wanted to elucidate this association by investigating whether schizophrenia in offspring increases the risk of Alzheimer's dementia. Methods: All individuals born between 1930 and 1953 were identified through national registers and followed from their 50th birthday until the date of Alzheimer's dementia, death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In total, 32 studies were excluded: 25 lacked necessary data, 10 14 , 16 20 , 32 46 one was a review, 47 five did not report dementia outcome, 21 25 and one was a sample duplication. 15 Finally, there were six papers including 206,694 cases of dementia and 5,063,316 participants in the meta-analysis 48 53 ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 32 studies were excluded: 25 lacked necessary data, 10 14 , 16 20 , 32 46 one was a review, 47 five did not report dementia outcome, 21 25 and one was a sample duplication. 15 Finally, there were six papers including 206,694 cases of dementia and 5,063,316 participants in the meta-analysis 48 53 ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“… 71 Moreover, there is evidence that the excess risk of dementia in subjects with schizophrenia may be explained by adverse health risk factors. 15 Thus, there are many potential reasons why people with schizophrenia may have progressive cognitive impairment during the course of the disease. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have addressed the familial coaggregation of the two disorders and have yielded incongruent results. [11][12][13][14][15] Narayanaswamy et al 16 reported significantly higher morbid risk for psychosis in early-onset dementia (EOAD) proband families and proposed a possibility of genetic overlap between dementia and psychosis. Thereby, in continuation of the proposal, there is a definite need to study the familial loading of dementia in families of patients with schizophrenia, to establish familial coaggregation.…”
Section: Original Articlementioning
confidence: 99%
“…This is in convergence to a recent population-based study which reported that schizophrenia proband families did not have an increased risk of Alzheimer's [incidence rate ratio (IRR), 0.97; 95% CI, 0.88-1.07], vascular, or unspecified dementia. 15 Rohde et al, 15 in turn, postulated that there might be no common etiological basis between the two disorders and that the associations detected between the two in previous studies might [11][12][13][14][15] be false because of higher rates of somatic comorbidity (like DM) among these individuals. But despite the increased proportion of somatic morbidity (like DM in schizophrenia probands families) in our study, there was nonreporting of MNCD.…”
Section: Original Articlementioning
confidence: 99%